1989
DOI: 10.1103/physrevlett.63.640
|View full text |Cite
|
Sign up to set email alerts
|

X-ray-photoelectron-diffraction investigation of strain at the Si/Ge(001) interface

Abstract: We describe a structural determination of pseudomorphic Si on Ge(OOl) by means of x-ray-photoelectron diffraction. By comparing the measured angular coordinates of the forward-scattering-induced [001] peak with those calculated by means of single-scattering theory, we find that the lattice constant perpendicular to the interface is 5.34 ±0.04 A. This value exceeds that predicted by elastic theory by 0.08 A.The effects of strain on the band offset at a semiconductor heterojunction are significant, yet they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The In-As bonds directly at the InAs/GaAs interface are thus stretched in order to conserve their bulk bond length [16]. The tendency towards conservation of the unstrained bulk bond length has in fact been suggested for rather different chemical environments [17][18][19][20][21]. Thus, while films of a few ML thickness are well described by macroscopic arguments, the atomic configuration at the interface can be understood only by considering the local properties of the crystal lattice, namely, the chemical bond.…”
Section: Gaas Structures the Results Shown In The Following Are Reprmentioning
confidence: 99%
“…The In-As bonds directly at the InAs/GaAs interface are thus stretched in order to conserve their bulk bond length [16]. The tendency towards conservation of the unstrained bulk bond length has in fact been suggested for rather different chemical environments [17][18][19][20][21]. Thus, while films of a few ML thickness are well described by macroscopic arguments, the atomic configuration at the interface can be understood only by considering the local properties of the crystal lattice, namely, the chemical bond.…”
Section: Gaas Structures the Results Shown In The Following Are Reprmentioning
confidence: 99%
“…On the other hand, information about the strain relaxation in the direction normal to the surface has so far been lacking. Although it has recently been demonstrated that high-energy x-ray photoelectron diffraction can be used to directly determine strain in the surface-normal direction at a strained, latticemismatched heterojunction [1,2], no method has so far been used to observe how the strain in this direction is relaxed as growth proceeds.This Letter reports the first in situ measurements of strain in the surface-normal direction during heteroepitaxy. For this purpose, we have used rocking-curve analysis of reflection high-energy electron diffraction (RHEED) based on dynamical diffraction theory, which has been used to determine atomic structures of crystal surfaces [3][4][5][6][7].…”
mentioning
confidence: 99%
“…In this case multiple-scattering-induced defocusing effects along [011] are particularly strong, as can be seen by comparing the calculated (singlescattering) peak intensity with experiment [36][37][38]. The reconstruction evidently has [85]. The presence eta substantial peak at 0 = 90 ° for the strained Si overlayer indicates agglomeration as a result of the high surface free energy of Si.…”
Section: The Role Of Surfactants In Promoting Epitaxymentioning
confidence: 91%
“…Nevertheless, an a~ value of 5.38 _ 0-08/~ can be derived from the R-factor curve. See [85] for more details.…”
Section: Surface Passivation By Heterojunction Formation 4221 Sexmentioning
confidence: 99%
See 1 more Smart Citation